Intersectional disparities in access to mental health services among youth aging out of foster care - Lauren Pryce McCarthy; Yanfeng Xu; Sally Hageman; Yao Wang (Child Protection and Practice)
Background: Youth aging out of the child welfare system lack support in accessing needed mental health care, as do youth of color and LGBTQ ​+ ​youth in the general population. Similar disparities may exist among youth aging out of foster care who hold intersecting social identities. Objective: This study aimed to explore the presence of mental health care access disparities among youth aging out of foster care using an intersectional lens. Participants: and Setting: The current study was a cross-sectional, exploratory analysis of secondary data from the Jim Casey Youth Opportunities Initiative (JCYOI) dataset. The sample included 2650 youth aging out of care. Methods: The current study utilized bivariate tests to explore the association between access to mental health care and key variables, a rate ratio to measure access disparities, and logistic regression to determine the main effect of identity on mental health care access. Findings: Lower rates of mental health care access were found among youth of color compared to White youth and among LGBTQ ​+ ​youth compared to non-LGBTQ ​+ ​youth. Disparities increased when youth of color also identified as LGBTQ+, however identity was not a significant predictor of mental health care access when controlling for insurance coverage and other variables. Conclusions: Disparities in access to needed mental health care found in the general population are also present among youth aging out of foster care. These findings suggest the need for targeted efforts from practitioners to ensure equitable access to mental health care for transition aged youth.